IDENTIFIKASI MUATAN GIZI DALAM MATA PELAJARAN DI SEKOLAH DASAR BANTARJATI 5 BOGOR - Resty Adhistiana; Ali Khomsan; Leily Amalia (Jurnal Gizi dan Pangan, 2009)
Education and nutrition support enhance each other. Nutrition education is an important thing that have to be integrated in school’s subject, because lack of knowledge regarding proper diet and healthy nutrition represents a major cause of implication in bad eating habits which can cause undernutrition  among school-age children. Therefore, healthy eating habits are important to establish during childhood and sustain thereafter. The objective of this study was to identified the nutrition material that integrated in elementary school’s subject. Cross sectional design was used in this study and four teacher of the fifth grade was interviewed by the researcher. The nutrition material in the subject was identified in qualitative and quantitative way. The result showed that only one topic that contain about nutrition which consist of two sub topic, human’s digestion system and the relationship between food and health. The material explanation in that two sub topic is include complete type and present in sentences and also picture type. The nutrition material was quantitatively attain 37.8% compared with IGD and PUGS as justification. It can conclude that nutrition material in elementary school’s subject was quite good.